2017
DOI: 10.22587/ajbas.2017.11.13.12
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Bio- desalination treatments of Mixed Sewage Water

Abstract: Background: The wastewater is known as a mixture of one or more kinds of different water such as domestic, comprising hospitals, industrial wastewater and agricultural water. Hypersaline environments are important for both surface extension and ecological significance. As all other ecosystems, they are impacted by pollution. However, the available information on the biodegradation of organic pollutants by halophilic microorganisms in such environments are quite limited. Moreover, it is well known that 5% of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…can be used as an e cient bio-removal of organic matters that reached to 80.49% and as a bio-sorbent of iron ions the removal rate reached to 79%. Moreover, 3 found that the biological treatment of saline wastewater with bacterial compound was effective in removal percentages of organic matter which reached to 79.8% and 63.2 to 84.0% for different heavy metal ions after 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…can be used as an e cient bio-removal of organic matters that reached to 80.49% and as a bio-sorbent of iron ions the removal rate reached to 79%. Moreover, 3 found that the biological treatment of saline wastewater with bacterial compound was effective in removal percentages of organic matter which reached to 79.8% and 63.2 to 84.0% for different heavy metal ions after 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…The reducing rate of salt water with MDCs in one cycle was found to be 43 +/-6%. 3 found that the bio-desalination treatment of saline wastewater by using bacterial compound reduced TDS to 39.0% after 4 days. Also, 8 found that the biological treatment with different free bacterial cells reduced TDS to 13.86% after 24 hrs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations